2020
DOI: 10.9734/cjast/2020/v39i630562
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Potential of Elaeis guineensis Plantations for Carbon Sequestration and Fresh Fruit Bunch Yield in Coimbatore, Tamil Nadu

Abstract: Elaeis guineensis is one of the potential carbon sequestering perennial crop by biological means. It has helped in the mitigating global warming and climatic fluctuations. The main objective of our study is to evacuate the hidden potential treasure of oil palm in carbon sequestration and vegetable oil yield. In this study we selected Tenera hybrids oil palm plantations in Coimbatore district of Tamil Nadu with standard management practices. It had been selected in the year 2019 and assessed for carbon s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
0
3
0
1
Order By: Relevance
“…The carbon benefits depends very much on the land use history, length or rotational fallow period, pedoagroclimatic conditions between sites, plantation management practices, irrigation practices and supply of nutrients influences the oil palm growth and the degree of disturbance during cultivation [8,29,24,28]. Rakesh et al [30] reported that among various parts of the plant, the trunk region sequestered the highest carbon and the trunk of a 5 year old oil palm sequestered 15.3 t Cha -1…”
Section: Trunkmentioning
confidence: 99%
See 2 more Smart Citations
“…The carbon benefits depends very much on the land use history, length or rotational fallow period, pedoagroclimatic conditions between sites, plantation management practices, irrigation practices and supply of nutrients influences the oil palm growth and the degree of disturbance during cultivation [8,29,24,28]. Rakesh et al [30] reported that among various parts of the plant, the trunk region sequestered the highest carbon and the trunk of a 5 year old oil palm sequestered 15.3 t Cha -1…”
Section: Trunkmentioning
confidence: 99%
“…Melling et al [34] stated that frond biomass significantly increased from 1.2 Mg ha -1 in 3 year old plantation to 20.5 Mg ha -1 in a ten year old plantation, after which it declined to 2.3 and 3.4 Mg ha -1 in 20 and 30 years old, respectively. Rakesh et al [30] reported that the fronds of a 5 year old oil palm sequestered 1.39 t C ha -1 whereas 10 year old oil palm sequestered 2.1 t C ha -1 .…”
Section: Frondsmentioning
confidence: 99%
See 1 more Smart Citation
“…En la actualidad los productores de palma de aceite y de otros cultivos como Coffea arabica L. y Theobroma cacao L. han buscado el pago por servicios ambientales al considerar que son sistemas agroforestales (CONANP, 2010), y en este contexto se ha estado considerando tal posibilidad al demostrarse en otras regiones del mundo que el cultivo de la palma tiene alto potencial para el secuestro atmosférico de CO2 (Leblanc et al, 2006;Rakesh et al, 2020), el cual es uno de los gases que va en aumento y con mayor contribución al calentamiento global, y en consecuencia, mitigar el efecto invernadero producto del incremento de las emisiones de gases generadas por el hombre (IPCC, 2000) en combinación con eventos naturales que inciden sobre la disminución de la vegetación (Watson et al, 2000).…”
Section: Introductionunclassified